Konflik Peran Ganda dan Manajemen Konflik pada Mahasiswi S1 yang Telah Menikah - Mar’atus Ratna Kurnia; Nur Eva; Pravissi Shanti (Fakultas Psikologi Universitas Negeri Malang, 2021)
The aims of this study is to reveal the multiple role conflict of undergraduate student who has been married and the solutions. This study used a qualitative method with case study model. Participants in this study were four married women who are still continuing their undergraduate study in Malang city. Data collection technique used was interview. The data analysis used is thematic analysis, while the validity is tested by using triangulation. The results of this study indicate that multiple role conflicts experienced by the married student are in the form of time-based conflict, strain-based conflict, and behaviour-based conflict. The multiple role conflict is caused by an additional role, the personality, the support of husband and parents, the demands of the environment, as well as the demands of the study task. The conflict management performed by the participants in this study is done through religious coping by doing worship, changing attitudes towards dual role, adjusting the time to do the dual role tasks, as well as relying on the dispensation of the study tasks.